A practical treatise on coal mining. Vol. 1 - Andre, George G. (E. & F.N. Spon, 1879)
The chapters of this 19th century treatise on coal mining engineering include information on geology, shaft-sinking, systems of working, haulage, drainage, ventilation and surface works.